2022
DOI: 10.4102/sajid.v37i1.363
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and distribution of selected cervical human papillomavirus types in HIV infected and HIV uninfected women in South Africa, 1989–2021: A narrative review

Abstract: Background: Human papillomavirus infection, a causative agent of cervical cancer, is of great concern, more so in populations with high HIV prevalence, such as South Africa.Aim: This review aimed to examine the prevalence and distribution of selected cervical human papillomavirus (HPV) types in HIV infected and HIV uninfected women in South Africa.Methods: PubMed and Web of Science databases were searched using key words. For data integrity, data was assessed by two authors independently. The study inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 127 publications
0
4
1
Order By: Relevance
“…Just like our study, several studies did not find any statistically significant association between condom use and HPV infection among FSWs [13,[20][21][22]34]. On the contrary, a study conducted in Benin and Mali found that condoms were able to protect against infection with HPV among FSWs (p = 0.004) [35].…”
Section: Human Papillomavirus Genotypingcontrasting
confidence: 53%
See 3 more Smart Citations
“…Just like our study, several studies did not find any statistically significant association between condom use and HPV infection among FSWs [13,[20][21][22]34]. On the contrary, a study conducted in Benin and Mali found that condoms were able to protect against infection with HPV among FSWs (p = 0.004) [35].…”
Section: Human Papillomavirus Genotypingcontrasting
confidence: 53%
“…The HPV genotyping was performed using an AmpFire HPV analyzer, Atila BioSystems, Sunnyvale, CA, USA. The AmpFire technology uses multiplex isothermal real-time fluorescence to detect HPV in cervico-vaginal specimens and it can genotype 15 high-risk types of HPV including types 16,18,31,33,35,39,45,51,52,53,56,58,59, 66, and 68 [16].…”
Section: The Study Typementioning
confidence: 99%
See 2 more Smart Citations
“…The findings for HPV-16 are in agreement with those from Castellsagué et al (41) and Edna Omar et al (42) concerning the HPV genotypes and cervical cancer cases. However, HPV-18 shows a higher prevalence in Botswana population (26,27,30,31) than in the reported studies (43,44). Although the majority of HPV infections in early ages clear spontaneously (45, 46), some do become chronic infections and may potentially evolve to malignant transformation of the cervix.…”
Section: Discussionmentioning
confidence: 92%